Associations Between Hip Pathology, Hip and Groin Pain, and Injuries in Hockey Athletes: A Clinical Commentary - Matt Kelly; Josh Secomb (International Journal of Sports Physical Therapy)
Femoroacetabular impingement (FAI), particularly cam morphology, is highly prevalent among elite hockey athletes. Moreover, hip and groin pain has become a common issue in hockey, with approximately 50% of European professional athletes reported to experience a hip or groin problem during a season. While most athletes will not miss training or competition due to this, restricted competitive performance and increased risk of reduced physical and psychological well-being are likely. Recent research suggests that the development of cam morphology is related to the repetitive shear stresses experienced at the hip joint during adolescence from skating. This condition likely increases the potential for intra-articular and extra-articular injuries in these athletes later in their careers. Research also indicates that the hip joint mechanics during forward skating substantially increase the possibility of sustaining a labral tear compared to other sports. Such an injury can increase femoral head movement within the joint, potentially causing secondary damage to the iliofemoral ligament, ligamentum teres and joint capsule. These injuries and the high density of nociceptors in the affected structures may explain the high prevalence of hip and groin pain in hockey athletes. Compensatory adaptations, such as reduced hip strength, stability, and range-of-motion (ROM) likely increase the opportunity for core muscle injuries and hip flexor and adductor injuries. Specifically, the limited hip ROM associated with cam morphology appears to exacerbate the risk of these injuries as there will be an increase in pubic symphysis stress and transverse strain during rotational movements. It is hoped that this article will assist practitioners currently working with hockey athletes to develop evidence-informed monitoring strategies and training interventions, aimed at reducing the incidence and severity of hip and groin problems, ultimately enhancing athlete performance and well-being. Therefore, the purpose of this clinical commentary was to examine current evidence on common hip pathologies in hockey athletes, exploring potential associations between hip and groin pain and the biomechanics of hockey activities.